Feminization of African agriculture and the meaning of decision-making for empowerment and sustainability - Haug, R.; Mwaseba, D. L.; Njarui, Donald M.G.; Moeletsi, M.; Magalasi, M.; Mutimura, Mupenzi; Hundessa, F.; Aamodt, Julie T (MDPI, 2021)
The purpose of this study was to assess women’s decision-making power in small-scale agriculture in six African countries in view of the feminization of agriculture and to discuss the meaning of decision-making in relation to women’s empowerment and sustainability. The data are drawn from a multisite and mixed-method agricultural research and development project in six sub-Saharan countries including two sites in each country. The five domains of empowerment outlined in the Women’s Empowerment in Agriculture Index are used to structure the analysis. The results indicate that in the selected sites in Malawi, Rwanda and South Africa, women farmers tend to dominate agricultural decision-making, while the result is more mixed in the Kenyan sites, and decision-making tends to be dominated by men in the sites in Tanzania and Ethiopia. Despite women participating in agricultural decision-making, the qualitative results show that women small-scale farmers were not perceived to be empowered in any of the country sites. It appears that the feminization of agriculture leads to women playing a more important role in decision-making but also to more responsibilities and heavier workloads without necessarily resulting in improvements in well-being outcomes that would enhance sustainability.